(untitled) (American Journal of Technology and Applied Sciences, 2024)
This article analyzes the word-forming suffixes of the noun, adjective, verb and adverb word classes in English and Uzbek. The weights of noun and adjective suffixes in English are determined by numerical coefficients and the weights of noun and adjective suffixes corresponding to Uzbek are determined by numerical coefficients, the weights of the corresponding suffixes in the two languages are compared, and the affixes of verb and adverb word classes in the two languages and their grammatical differences are discussed with examples. The comparative analysis of word groups in English and Uzbek is explained in detail in the comments that word affixes play a significant role in the level of abstraction and quality of text translation performed in two languages in computer translation.